Effect of roasted barley flour on lipid metabolism and gut fermentation in mice fed high-fat diets. (November 2021) - Mio, Kento; Yamanaka, Chiemi; Kohyama, Noriko; Ichinose, Yasunori; Yanagisawa, Takashi; Aoe, Seiichiro
Abstract: We investigated the compositional changes in β-glucan and other nutrients in roasted barley flour by comparing them to untreated barley flour. We also examined whether the intake of roasted barley flour improved lipid metabolism and gut fermentation of barley β-glucan using obese mice fed high-fat diets supplemented with cellulose, untreated barley flour, and roasted barley flour. The molecular weight (MW) of β-glucan in roasted barley flour was reduced by approximately 16%–49% when compared to the untreated barley flour, but the content of β-glucan was not changed. Resistant starch and damage starch were increased in the roasted barley flour. Lipid metabolism was improved in C57BL/6J mice fed roasted barley flour when compared to cellulose. Short-chain fatty acids (SCFAs) were also increased in the cecum of mice fed roasted barley flour compared with untreated barley flour. These results indicated that the roasting process of barley grain caused a reduction in the MW of β-glucan, but the improving effects on lipid metabolism was enhanced through a prebiotic action promoted by SCFAs. Graphical abstract: Image 1 Highlights: Roasted barley flour lowers the molecular weight of beta-glucan but does not change its content. Roasted barley flour increases the damaged starch and resistant starch. Mice fed roasted barley flour increase short-chain fatty acids in their cecum compared to mice fed untreated barley flour. Intake of roasted barley flour improves lipid metabolism mediated by prebiotic effect in mice.